Distribution of branched glycerol dialkyl glycerol tetraether (brGDGT) lipids from soils and sediments from the same watershed are distinct regionally (central Chile) but not globally - O’Beirne, Molly D.; Scott, Wesley P.; Contreras, Sergio; Araneda, A.; Tejos, E.; Moscoso, J.; Werne, Josef P. (Frontiers in Earth Science, 2024)
Quantitative reconstructions of past continental climates are vital for understanding contemporary and past climate change. Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are unique bacterial lipids that have been proposed as universal paleothermometers due to their correlation with temperature in modern settings. Thus, brGDGTs may serve as a crucial paleotemperature proxy for understanding past climate variations and improving regional climate projections, especially in critical but under constrained regions. That said, complications can arise in their application due to varying source contributions (e.g., soils vs peats vs lacustrine). As such, this study investigates brGDGT distributions in Chilean lake surface sediments and corresponding watershed soils to determine the source of brGDGTs to lake sediments. Global datasets of brGDGTs in lake sediments and soils were additionally compiled for comparison. Distinct brGDGT distributions in Chilean lakes and soils indicate minimal bias from soil inputs to the lacustrine sediments as well as in situ lacustrine production of brGDGTs, which supports the use of brGDGTs in lake sediments as reliable paleotemperature proxies in the region. The ΣIIIa/ΣIIa ratio, initially promising as a brGDGT source indicator in marine settings, shows global complexities in lacustrine settings, challenging the establishment of universal thresholds for source apportionment. That said, we show that the ratio can be successfully applied in Chilean lake surface sediments. Direct comparisons with watershed soils and further research are crucial for discerning brGDGT sources in lake sediments and improving paleotemperature reconstructions on regional and global scales moving forward. Overall, this study contributes valuable insights into brGDGT variability, essential for accurate paleoreconstructions.